Assessing the Impact of Principal Leadership and Teacher Performance on Educational Quality: The Role of TQM as a Mediator - Nurul Hidayatul Mukaromah; Athok Fuadi; Rihab Wit Daryono (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This research investigates the influence of the principal's leadership and teacher performance on the quality of education and the mediating role of TQM in this relationship. Random sampling techniques were used to sample 50 MA Darul Falah Sukorejo Ponorogo teachers. Data collection was carried out using a questionnaire consisting of a 5-point Likert scale. PLS-SEM analysis was used to analyze data and test the conceptual model. The research results show that teacher performance significantly improves education quality but not principal leadership's influence. Apart from that, TQM mediates in increasing the influence of the principal's leadership on the quality of education (ρ=0.008) but not on the influence of teacher performance (ρ=0.703). The research implications emphasize the development of organizational culture supported by TQM and teacher professional training and development. So, building an organizational culture that supports TQM principles is essential. It involves a commitment from all levels of management, including principals and administrative staff, to prioritize educational quality and continuous improvement. Provide regular training to teachers on TQM concepts, practices, and strategies for implementing them in teaching and learning contexts.